UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL SIRIH CINA (PEPEROMIA PELLUCIDA) DENGAN MENGGUNAKAN METODE DPPH - Aini, Nurul; Ginting, Astriani Natalia Br.; Kaban, Vera Estefani (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Chinese betel (Peperomia pellucida L.) is a plant known to contain various secondary metabolites with potential antioxidant activity. This study aimed to identify the bioactive compounds present in the ethanol extract of Chinese betel and to evaluate its antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Extraction was performed using 96% ethanol and yielded an extract recovery of 8.75% from 400 grams of simplicia. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, and triterpenoids/steroids, while saponins were not detected. Antioxidant activity was evaluated at five concentrations (20–100 ppm) with vitamin C used as a reference standard. The IC₅₀ value of the Chinese betel ethanol extract was 63.49 ppm, indicating strong antioxidant activity, whereas vitamin C showed an IC₅₀ value of 6.06 ppm, classified as very strong antioxidant activity. Based on these findings, the ethanol extract of Chinese betel shows potential as a natural antioxidant source and warrants further investigation for the development of natural product-based formulations.